Penggunaan Media Sosial Instagram dalam Pembelajaran Kanji - Muhlisian, Asep Achmad; Putri, Yuliani Kusuma (Journal of Japanese Language Education and Linguistics, 2019)
This research entitled " Use of Instagram in Kanji Learning, sees that still many students who have difficulty in learn kanji, especially in remembering kanji caused by several things based on preliminary observations of the lack of interest of Japanese students in kanji and many consider it is difficult to learn kanji. The object of this research is the 5th semester Japanese language students who are actively using Instagram. This research used action research method. Data analysis result showed that of the 435 students who posted kanji via Instagram, most of them used features on Instagram and adjusted them to their ability to remember kanji, such as by association of images, interesting videos and videos of kanji writing sequences.